Narrative thinking and historical knowledge: a case study in Early Childhood Education working on Prehistory - IAnson Gutiérrez, Sara; Suárez Suárez, Miguel Ángel; Calaf Masachs, Roser (Clio. History and History Teaching, 2024)
The study revolves around an educational experience in a school with ten preschool students (between five and six years old) in Asturias (Spain) and learning prehistory. Using a participatory, experiential and research-based methodology, we analyse their evolution in understanding the specific contents of the evolution of hominids and the development of their narrative thinking to reconstruct their discourse, with emphasis on temporal operators (sequencing/succession, simultaneity, duration/rhythm, temporal orientation, periodisation and, permanence, changes and consequences). For this purpose, qualitative research is carried out using participant observation during the teaching-learning process and the sequencing of images accompanied by interviews that capture embryonic capacities.